Infant Feeding Method and Body Composition Differences at 6 Months. (14th June 2022) - Herman, Amy; Hull, Holly; Sullivan, Debra; de Santiago, Laura Castro; Horton, Sarah
Abstract: Objectives: Explore how feeding method is related to distribution of fat and fat free mass in infants at 6 months of age. Methods: This is a secondary data analysis of an RCT assessing prenatal DHA supplementation on infant growth. At 6 months of age, DXA measured infant body composition and distribution. Total body less head (TBLH) was used. Feeding method was collected by questionnaire. Infants were split into groups of breastfeeding (BF; n = 56), combo (C; n = 14), or formula feeding (F; n = 44). A 24-hour dietary recall was performed and NDSR was used to determine nutrient totals. Nutrients in breastmilk were homogenously estimated using the human milk option in NDSR, and a standard intake volume was assumed for those feeding directly from the breast. One-way ANOVA determined differences between the groups. Results: BF infants consumed the lowest calories (BF: 557 ± 108; C: 785 ± 173; F: 753 ± 169; P < 0.01) and weighed less than F fed infants (7.73kg ± 0.87 vs 8.06kg ± 1.10 respectively; P < 0.05). However, BF infants consumed the highest percentage of calories from fat at 51.8% ± 3.7 (compared to C: 47.2% ± 4.7; F: 46.3% ± 3.8; P < 0.01) and had higher percentage body fat (%fat; BF: 38.5% ± 4.7 C: 32.8% ± 4.3; F: 35.9% ± 3.4) and central %fat (BF: 27.3% ± 4.8; C: 23.3% ± 4.3; F: 24.0% ± 3.9; all pairwise P < 0.01). BF infants had 0.14kg higher central and 0.32kg higher peripheral fat mass than combo (P < 0.05) but not formula feeders, although central fat mass between BF and F approached significance (mean difference 0.07kg; p = 0.054). Central fat-free mass was different between the BF and F groups only, with BF having 0.22kg lower fat-free mass (P < 0.01). There were no significant differences between the groups in peripheral fat-free mass. Conclusions: Feeding method at 6 months of age is related to body composition and distribution. Although breastfeeding infants weighed less and consumed less calories, they had higher total and central %fat. Funding Sources: This project was supported by an NIH NIDDK R01 grant.